Before Westphalia: Imagining An Alternative Asian Globalization - Noor, Farish (Muslim Politics Review, 2023)
The world order as it is known and understood today was built upon the foundations of imperialism and colonialism. It must be acknowledged that the very epistemologies and vocabularies that we use in the domains of diplomacy, international relations and politics are part of the legacy of Empire as well. This paper asks, is it possible for us to rethink and/or re-imagine an alternative global system that reconnects with the realities of socio-economic and socio-political life across the Asian continent and the world of the Indian Ocean prior to the arrival of Western imperialism? And, if that is indeed possible, would this also open up new opportunities for us to imagine the manner through which we – as postcolonial Asian and African scholars and subjects – represent ourselves and the ‘Western Other’?